2021
DOI: 10.1155/2021/6614191
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Diagnosis of White Matter Softening in Premature Infants Based on Electroencephalogram (EEG)

Abstract: Periventricular white matter softening in preterm infants can lead to severe sequelae and greatly affects the quality of life of preterm infants, and early diagnosis is of great clinical significance and value. The purpose of this study is to select a diagnostic test scientifically and rationally, to interpret and evaluate the results of the diagnostic test, and to evaluate the selected diagnostic method. Although DWI is a sensitive method for early diagnosis of PVL, it is not suitable for critical preterm inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%